THE INFLUENCE OF MARKETING CREATIVITY DIMENSIONS ON MARKETING PERFORMANCE - Rohmad Prio Santoso (Media Inovasi Pendidikan dan Publikasi, 2024)
This study aims to explore the influence of creativity dimensions namely Opportunity Creator, Innovation, and Risk Taking on marketing performance in the context of the company. These dimensions are important elements in determining how marketing creativity can influence the effectiveness and efficiency of marketing strategies. Opportunity Creator refers to the ability to create and capitalise on new market opportunities, Innovation refers to the implementation of new ideas that increase the added value of products or services, while Risk Taking involves making risky decisions in an effort to pursue new opportunities. This research uses a quantitative method with a survey approach with a sample size of 60 respondents, to collect data obtained from MSMEs located in the SLG Gumul area of Kediri City, and data analysis techniques are carried out using (SEM) structural equation modelling with the help of Smart PLS software to evaluate the relationship between creativity dimensions and marketing performance. The study results show that the three dimensions of creativity significantly affect marketing performance. Consisting of Opportunity Creator and Innovation have a strong positive impact on marketing performance, while Risk Taking also shows a positive influence but in a more measured context. The findings provide valuable insights for marketing managers on the importance of integrating creativity dimensions in their marketing strategies and offer a basis for further research on how risk-taking and innovation can be optimised to improve marketing performance.